Culture circles on social and environmental determinants: action research with community health agents of Paraisópolis, SP - Francisco Nilson Paiva dos Santos; Renata Ferraz de Toledo (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objectives: To identify social and environmental determinants of health in the perception of community health agents, and to develop a health education process to contribute to the improvement of health promotion. Methods: A qualitative action research based on Freire's Research Itinerary (Culture Circles), using talking maps and integrated panels, with 29 community health agents of the Paraisópolis II Basic Health Unit, in the community of Paraisópolis, Sao Paulo. The analysis of the results was carried out by the Method of Triangulation. Results: Sanitation, housing, behaviors, health services, and other social facilities were identified, which, along with the representation of blaming, were codified and decoded by the integration of technical and traditional knowledge. Conclusions: Knowledge, values and abilities related to social and environmental determinants and their applicability in the Family Health Strategy, as well as the importance of community strengthening for health promotion and for coping with health vulnerabilities and inequities, were critically unveiled.